2016
DOI: 10.1002/1873-3468.12424
|View full text |Cite
|
Sign up to set email alerts
|

Enhancers and their dynamics during hematopoietic differentiation and emerging strategies for therapeutic action

Abstract: Edited by Wilhelm JustCellular differentiation requires precisely regulated tissue-specific and developmental stage-specific gene expression patterns. Numerous studies have highlighted the predictive power of enhancers on lineage-specific gene expression programs and have started to unravel their mechanisms of action. We review here the dynamics of the enhancer landscape during hematopoietic differentiation and how enhancers function in the context of the 3D organization of the genome. We further discuss the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 142 publications
(264 reference statements)
0
7
0
Order By: Relevance
“…Putative enhancers are characterized by the presence of H3K4me 1 histone modifications. In the absence of H3K27ac, these enhancers are termed “poised” or “primed” enhancers (36, 53). The presence of H3K27ac modifications defines “active” enhancers that positively regulate transcription of their target genes (36, 53, 54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Putative enhancers are characterized by the presence of H3K4me 1 histone modifications. In the absence of H3K27ac, these enhancers are termed “poised” or “primed” enhancers (36, 53). The presence of H3K27ac modifications defines “active” enhancers that positively regulate transcription of their target genes (36, 53, 54).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of H3K27ac, these enhancers are termed “poised” or “primed” enhancers (36, 53). The presence of H3K27ac modifications defines “active” enhancers that positively regulate transcription of their target genes (36, 53, 54). Our data showed that Ikaros binding to DNA can either induce de novo formation of active enhancers (transforming H3K4me 1 –/H3K27ac– DNA sites into H3K4me 1 +/H3K27ac+ sites) or activate “poised” enhancers (H3K4me 1 +/H3K27ac–).…”
Section: Discussionmentioning
confidence: 99%
“…They also highlight the key role of signaling pathways and transcription factors during the endothelial to hematopoietic transition, the crucial transdifferentiation process at the origin of HSCs . The second topic covers the molecular control of hematopoietic specification and differentiation, embracing genetic programming, chromatin landscape regulation, epigenetic regulation, and the dynamics of enhancer landscape . The third topic covers the recent progresses made toward developing new techniques (e.g.…”
mentioning
confidence: 99%
“…An initial key observation stems from the analysis of globin genes, where it was found that mammalian gene transcriptional regulation is under the control of distal regulatory elements (e.g., enhancers) that can be located tens of kilobases away from promoters. The discovery of the globin locus control region (LCR) is one such example, and this peculiar feature was subsequently generalized, years after, with the development of high throughput chromatin profiling assays (such as ChIP-Seq, DNAse-Seq, and related assays thereof), which unraveled the complexity of the mammalian regulatory landscape [ 3 , 4 , 5 ].…”
Section: Erythroid Epigenetics: Chromatin Landscape and 3d Chromosoma...mentioning
confidence: 99%